Young Children Are Wishful Thinkers: The Development of Wishful Thinking in 3‐ to 10‐Year‐Old Children. Issue 4 (9th August 2019) - Wente, Adrienne O.; Goddu, Mariel K.; Garcia, Teresa; Posner, Elyanah; Fernández Flecha, María; Gopnik, Alison
Abstract : Previously, research on wishful thinking has found that desires bias older children's and adults' predictions during probabilistic reasoning tasks. In this article, we explore wishful thinking in children aged 3‐ to 10‐years‐old. Do young children learn to be wishful thinkers? Or do they begin with a wishful thinking bias that is gradually overturned during development? Across five experiments, we compare low‐ and middle‐income United States and Peruvian 3‐ to 10‐year‐old children ( N = 682). Children were asked to make predictions during games of chance. Across experiments, preschool‐aged children from all backgrounds consistently displayed a strong wishful thinking bias. However, the bias declined with age.